Development and Validation of HPTLC Method for Estimation of Carbamazepine in Formulations and Its In Vitro Release Study. (20th September 2010) - Patel, Rashmin B.; Patel, Mrunali R.; Bhatt, Kashyap K.; Patel, Bharat G.
Abstract : A new, simple, and rapid high-performance thin-layer chromatographic method was developed and validated for quantitative determination of Carbamazepine. Carbamazepine was chromatographed on silica gel 60F 254 TLC plate using ethyl acetate-toluene-methanol (5.0 + 4.0 + 1.0 v/v/v) as mobile phase. Carbamazepine was quantified by densitometric analysis at 285 nm. The method was found to give compact spots for the drug (R f = 0 . 47 ± 0.01). The linear regression analysis data for the calibration plots showed good linear relationship withr 2 = .9995 in the concentration range 100–600 ng/spot. The method was validated for precision, recovery, repeatability, and robustness as per the International Conference on Harmonization guidelines. The minimum detectable amount was found to be 16.7 ng/spot, whereas the limit of quantitation was found to be 50.44 ng/spot. Statistical analysis of the data showed that the method is precise, accurate, reproducible, and selective for the analysis of Carbamazepine. The method was successfully employed for the estimation of equilibrium solubility, quantification of Carbamazepine as a bulk drug, in commercially available preparation, and in-house developed mucoadhesive microemulsion formulations and solution.